Faktor-Faktor Yang Mempengaruhi Minat Investasi Investor Muda Di Pasar Modal Syariah - Maharani, Nadia; Apria Ningsih , Putri; Anggraini , Dessy (Manajemen Keuangan Syariah, 2025)
This study aims to explain how the influence of investment returns, investment risks, investment knowledge, motivation on the investment interest of young investors in the sharia capital market at PT. FAC Securities Jambi Branch. The type of research used is quantitative research. The sampling technique in this study uses purposive sampling. The population used is young investors aged less than 31 years who are registered as active sharia investors at PT. FAC Securities Jambi Branch and based on the solvin formula the number of samples obtained in this study is 96 respondents. Data obtained from the results of distributing questionnaires processed through the SPSS application. Data analysis methods used in this study include testing research instruments, classical assumption tests, hypothesis tests and multiple linear regression tests. The results of this study can be concluded that partially shows that the investment return variable (X1) has an effect on investment interest, the investment risk variable (X2) has an effect on investment interest, the investment knowledge variable (X3) has no effect on investment interest and the motivation variable (X4) has an effect on investment interest. This study also simultaneously shows that the investment return variable (X1), investment risk (X2), investment knowledge variable (X3) and motivation (X4) have an effect on investment interest of young investors to invest in the sharia capital market at PT. FAC Securities Jambi Branch.